Linguophilosophical Bases of Times Intersection in Documentary Artistic Prose of Svetlana Aleksievich - Arzieyva, Yevgeniya (Przegląd Wschodnioeuropejski, 2018)
The article touches on the problem of the intersection of temporal layers and the interdependence of time and space, transmitted in modern documentary and artistic prose through a palette of language tools. This problem is considered on the material of the work of Svetlana Aleksievich “Chernobyl Prayer”, in which the tragic event in the territory of Eastern Europe (modern Ukraine), which was the techno genic catastrophe at the Chernobyl nuclear power plant, is transmitted in the form of the polyphony of its involuntary participants. Fragments of the past in the Christian picture of the world are interpreted by the author of the work in the context of the philosophy “for our sins”, against which the temporal perspective of the participants of the event is presented as an apocalypse. The complex of linguistic means in combination with the genre singularity allows us to convey the main idea of the work that the gap in time leads to the collapse of the single space that the Soviet Union was.